Biodiversity and distribution of selected freshwater mollusks and crayfish along a mineralization gradient in the Zarafshan River, Uzbekistan - KHUSNIDDIN BOYMURODOV; JONIBEK SAIDKULOV; SAYFULLA KHORAZOV; TOZAGUL JABBOROVA; BOBUR SABOXIDDINOV; OMON MIRZAMURODOV; BAXTIYOR ALIYEV; SULTON SUYAROV; BEKZOD OTAKULOV; AZAMAT EGAMKULOV; NADIR KHASANOV; FARRUKH DJALILOV; SUKHROB BOYMURODOV; MATNAZAR RAXIMOV; ZUVAIDULLO IZZATULLAEV; KHUDAINAZAR YUNUSOV; ZAFARJON MUSTAFOYEV (Society for Indonesian Biodiversity, 2026)
Abstract. Boymurodov K, Yunusov K, Izzatullaev Z, Raximov M, Boymurodov S, Djalilov F, Khasanov N, Egamkulov A, Otakulov B, Suyarov S, Aliyev B, Mirzamurodov O, Saboxiddinov B, Jabborova T, Khorazov S, Saidkulov J, Mustafoyev Z. 2026. Biodiversity and distribution of selected freshwater mollusks and crayfish along a mineralization gradient in the Zarafshan River, Uzbekistan. Biodiversitas 27 (4): d270425. https://doi.org/10.13057/biodiv/d270425. The Zarafshan River basin is characterized by a distinct hydro-chemical gradient shaped by intense urbanization and industrial activity, which significantly impacts its biological integrity. This study evaluates the taxonomic diversity and distribution of four key freshwater macroinvertebrate families (Unionidae, Corbiculidae, Lymnaeidae, and Astacidae) along a documented mineralization gradient in the Zarafshan River basin. Field surveys were conducted from 2023 to 2025 at 12 sampling stations representing varying anthropogenic pressures. Taxonomic composition was analyzed alongside hydro-chemical parameters, including Total Dissolved Solids (TDS) and nutrient levels. A total of 11 species, belonging to 3 classes, 4 orders, 4 families, and 7 genera, were identified. Data analysis revealed a marked decline in both species’ richness and individual density as water mineralization increased from 300 mg/L (Site Z1) to 1600 mg/L (Site Z4). Ecological classification identified the predominance of phytophilic (5 species, 45.4%) and peloreophilic (3 species, 27.3%) groups. Faunistic similarity analysis, using Jaccard and Ochiai indices, showed the highest similarity between stations K1 and A2 (Ochiai 0.95), while the lowest similarity was recorded between the most impacted stations Z4 and K4 (Jaccard 0.45). The observed spatial shifts in community structure suggest that elevated mineralization and organic loading are primary drivers of macroinvertebrate distribution in the basin. These findings characterize the environmental tolerances of the target taxa, providing foundational data for developing future bioindication frameworks in the Zarafshan River ecosystem.